Technology and Adolescent Mental Health (Springer International Publishing, 2018)
This comprehensive book provides a framework for healthcare providers working with the dual challenges and opportunities presented by the intersection of mental health and technology. Technology and Adolescent Mental Health provides recent, evidence-based approaches that are applicable to clinical practice and adolescent care, with each chapter including a patient case illustrating key components of the chapter contents. Early chapters address the epidemiology of mental health, while the second section of the book deals with how both offline and online worlds affect mental health, presenting both positive and negative outcomes, and focusing on special populations of at-risk adolescents. The third section of the book focuses on technology uses for observation, diagnosis or screening for mental health conditions. The final section highlights promising future approaches to technology, and tools for improving intervention and treatment for mental health concerns and illnesses. This book will be a key resource for pediatricians, family physicians, internal medicine providers, adolescent medicine and psychiatry specialists, psychologists, social workers, as well as any other healthcare providers working with adolescents and mental health care.